2022
DOI: 10.3389/fnut.2022.981533
|View full text |Cite
|
Sign up to set email alerts
|

Combined systemic inflammatory immunity index and prognostic nutritional index scores as a screening marker for sarcopenia in patients with locally advanced gastric cancer

Abstract: BackgroundSarcopenia is associated with poor clinical outcomes in patients with locally advanced gastric cancer (LAGC). Currently, the diagnostic criteria for sarcopenia are complex and laborious. Increased evidence suggests the inflammatory state of the body is closely associated with the development of sarcopenia. The systemic immune-inflammatory index (SII) and the prognostic nutritional index (PNI) are representative blood indicators of the status of the systemic inflammatory response, but the clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Many studies paid more attention to the role of nutrition in sarcopenia and surgery (35)(36)(37). A prospective study from China showed that the combined systemic inflammatory immunity index and prognostic nutritional index scores as an indicator of nutrition status may predict the incidence of sarcopenia for patients with advanced gastric cancer who underwent radical surgical resection (38). Moreover, a cohort study conducted in Japan reported that the protein intake may affect the skeletal muscle mass of patients who underwent kidney transplantation, and suggested that a protein intake of more than 0.72 g/kg IBW/day may provide the patients with improved skeletal muscle mass (37).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies paid more attention to the role of nutrition in sarcopenia and surgery (35)(36)(37). A prospective study from China showed that the combined systemic inflammatory immunity index and prognostic nutritional index scores as an indicator of nutrition status may predict the incidence of sarcopenia for patients with advanced gastric cancer who underwent radical surgical resection (38). Moreover, a cohort study conducted in Japan reported that the protein intake may affect the skeletal muscle mass of patients who underwent kidney transplantation, and suggested that a protein intake of more than 0.72 g/kg IBW/day may provide the patients with improved skeletal muscle mass (37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that combining SII with PNI to form a SII-PNI score can more fully reflect a patient's immune status. We found that to date, only four studies have reported on SII-PNI score predicting treatment outcomes in patients with gastric cancer and urothelial carcinoma (21)(22)(23)(24). They found that pre-treatment SII-PNI score was an important indicator of chemotherapy sensitivity in gastric cancer and urothelial carcinoma patients treated with combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…SII and PNI are two economical, readily available, and widely used hematological indexes. And the SII-PNI score, as a derivative index of them, can comprehensively reflect the immune status of patients and has been used to evaluate the prognosis of patients with gastric cancer (21)(22)(23)(24). However, their clinical significance in patients with advanced NSCLC is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we introduce the systemic immune-inflammation index (SII), which is a combination of neutrophil, lymphocyte, and platelet counts in blood. Also, it has been widely investigated and shown to be a useful prognostic indicator in various solid tumors including hepatocellular carcinoma ( 10 ), small cell lung cancer ( 11 ), gastroesophageal adenocarcinoma ( 12 , 13 ), renal cell carcinoma ( 14 ), and prostate cancer ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%